2004
DOI: 10.1007/s00122-004-1669-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the genetic bases of natural variation in tomato leaf, sepal, and petal morphology

Abstract: In an effort to better understand the dramatic differences in vegetative and floral morphology that differentiate species within the genus Lycopersicon, quantitative trait loci (QTL) for leaflet and perianth size and shape characters were mapped in an interspecific F2 population of tomato (Lycopersicon esculentum x L. pennellii). Thirty-six highly significant (P < or = 0.001) QTL were associated with 18 separate traits. QTL for correlated traits were generally not colocalized in the genome unless there was a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 43 publications
5
32
0
Order By: Relevance
“…In agreement with previous comparative QTL mapping studies for leaf and floral traits (Frary et al, 2004;Juenger et al, 2005), the single leaf-size QTL we detected did not overlap with any of the loci found to influence petal growth. Also, there was no genetic correlation between leaf and petal size in our population.…”
Section: Genetics Of Selfing-syndrome Traitssupporting
confidence: 92%
“…In agreement with previous comparative QTL mapping studies for leaf and floral traits (Frary et al, 2004;Juenger et al, 2005), the single leaf-size QTL we detected did not overlap with any of the loci found to influence petal growth. Also, there was no genetic correlation between leaf and petal size in our population.…”
Section: Genetics Of Selfing-syndrome Traitssupporting
confidence: 92%
“…The analysis of natural variation in a recombinant inbred line built from A. majus and the wild species A. charidemi shows that several QTL controlling floral size are specific for the flower, confirming a partial separation of vegetative and reproductive control (A. Hudson personal communication). A recent survey of QTL controlling leaf, sepal and petal size in tomato has shown that there is no overlap between QTL controlling the same trait in different organs (Frary et al, 2004). These results seem to be also true in Arabidopsis where a comparison of QTL affecting leaf and floral development have found eleven QTL that affect only one of the organs and two that have pleiotropic effects (Juenger et al, 2005).…”
mentioning
confidence: 91%
“…Such phenotypes are associated with water use efficiency and thermoregulation, traits important to yield (Nicotra et al, 2011;Chitwood et al, 2012a). Studies examining leaf morphology are often limited to analyses of size, dimensions of length and width, and complexity (Jiang et al, 2000;Pérez-Pérez et al, 2002;Holtan and Hake, 2003;Frary et al, 2004). Recently, a genome-wide association study using the maize (Zea mays) nested association mapping population identified liguleless genes as regulators of upright leaf angles.…”
Section: Introductionmentioning
confidence: 99%